Studi Analisa Pengaruh Total Harmonic Distortion (THD) terhadap Rugi-Rugi, Efisiensi, dan Kapasitas Kerja Transformator pada Penyulang Kerobokan - Adi Wirajaya, I Putu; Rinas, I Wayan; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2019)
Kerobokan feeder supply electrical energy in the area of Kerobokan. This feeder supplies 67 distribution transformers that serve a variety of customers with nonlinier electrical loads. Nonlinier electrical loads cause harmonics which adversely affect customers and power system equipment, especially distribution transformers. In Kerobokan feeder, only 3 (4.5%) of the 67 transformers has THDi content that according with the IEEE 519-2014 standard and 64 (95.5%) of the 67 transformers has a high THDi content and exceed the IEEE 519-2014 standard. For this reason, the power losses, efficiency, and work capacity of the transformer are analyzed due to the effect of THDi. This study uses a direct measurement method in all transformers in the Kerobokan feeder and simulation on the ETAP Powerstation program. The results of the analysis showed that total power losses without being affected by THDi for all transformers were 49.4 kW and after being affected by THDi were 591.71 kW. The highest THDi content is in the KA 0992 transformer is 24.8% which results in an increased in power losses is 12.02 kW or 12.02% of its capacity and a decreased in efficiency is 12.66% and has a decreased in work capacity is 19.9%. While the smallest THDi content is found in the DB 449 transformer is 6.8% which results in an increased in power losses is 2.2 kW or 0.88% of its capacity and a decreased efficiency is 1.01% and has a decreased in work capacity is 2.7%.